Shock absorbing bumper and method of manufacturing the same
By curing solid salt and molten metal to form porous metals and surrounding the resin composite to fill its pores, the bumper for impact absorption is solved, and the limitations of existing resin composite bumpers in thickness and impact absorption are reduced, and the manufacturing cost of foam metal manufacturing is achieved, achieving more efficient impact energy absorption and lighter vehicle weight.
Patent Information
- Application Number
- CN201911064995.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-12
- Filing Date
- 2019-11-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2039-11-04
AI Technical Summary
The bumpers made of existing resin composite materials have limitations in thickness and impact absorption, and are difficult to apply to front bumpers of high severity. At the same time, the foam metal manufacturing method has problems such as high manufacturing cost and low removal rate.
By filling the solid salt in the mold and solidifying the molten metal with the solid salt, a porous metal is formed, and then the resin composite is surrounded by the porous metal to fill its pores to create a bumper for impact absorption.
It achieves a lighter weight than conventional steel bumpers, while improving impact energy absorption efficiency, is suitable for front bumpers, and produces porous metals through cheap solid salt and water, reducing manufacturing costs.
Smart Images

Figure CN112078526B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2019-69190, filed on Jun. 12, 2019, which is hereby incorporated by reference in its entirety. Field of the Invention
[0003] The present disclosure relates to a bumper for increasing impact energy absorption efficiency and a method of manufacturing the same. Background Art
[0004] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.
[0005] Generally speaking, when a vehicle collides with an external object, the bumper of the vehicle plays the main role of absorbing impact energy to prevent damage to major components such as the engine and transmission, and to prevent injuries to vehicle occupants. Typically, the front of the vehicle is equipped with a steel bumper, and the rear thereof is equipped with a bumper made of a resin composite material, such as glass fiber mat reinforced thermoplastic (GMT), to reduce the weight of the vehicle. Specifically, the resin composite material such as GMT used in the rear bumper of the vehicle is 20% to 25% lighter than iron and has a strength similar to that of steel, so it is used to replace steel. In addition, since the resin composite material can be molded by injection molding, the resin composite material has a high degree of freedom in design to be applied to various automotive parts such as seats and bumpers.
[0006] In detail, Korean Patent No. 1,683,511 (Patent Document 1) discloses a glass fiber mat reinforced plastic composite material and a bumper back beam including a carbon fiber reinforced plastic composite material, which is staked in the glass fiber mat reinforced plastic composite material. However, resin composite materials such as GMT are plastic materials and have brittleness due to the properties of glass fibers or carbon fibers added as a reinforcing phase. As a result, a bumper made of a resin composite material has the following limitation in thickness: it is thicker than a conventional steel bumper so as to have an impact absorption rate similar to that of a conventional steel bumper. In addition, a bumper made of a resin composite material also has the following limitation: it is difficult to apply to a front bumper with a relatively high severity.
[0007] Meanwhile, a method of using foamed metal as a vehicle bumper has been proposed to reduce the weight of the vehicle. Specifically, Korean Publication Patent No. 2013-0052208 (Patent Document 2) discloses a method for manufacturing an open porous metal, which includes preparing a metal base material; preparing a mixed mold that does not react with the metal base material; preparing a spherical salt made of a non-metallic salt; dissolving the metal base material; injecting molten metal and the spherical salt into the mold; cooling the mold and separating the metal material from the cooled mold; and removing the spherical salt of the separated metal material. The manufacturing method disclosed in Patent Document 2 is limited in that the removal rate of the spherical salt is low due to the immersion of the metal material in warm water to dissolve and remove the spherical salt, and it is difficult to manufacture on a large scale. Summary of the invention
[0008] One aspect of the present disclosure provides a vehicle bumper for absorbing impact with a lighter weight than a conventional steel bumper and increasing impact energy absorption efficiency, thereby being applicable to a front bumper, and a method of manufacturing the same.
[0009] According to one aspect of the present disclosure, a method for manufacturing a bumper for impact absorption includes: filling a solid salt in a mold, injecting a molten metal into the mold, and solidifying the molten metal together with the solid salt to obtain a solidified product; spraying water onto the solidified product to dissolve the solid salt to obtain a porous metal having pores; arranging the porous metal in an injection mold; and injecting-inserting a resin composite material into the injection mold to surround the porous metal while filling at least a portion of the pores in the porous metal.
[0010] In addition, according to one aspect of the present disclosure, a bumper for impact absorption includes a porous metal and a resin composite material, wherein the resin composite material surrounds the porous metal while filling at least a portion of pores in the porous metal.
[0011] Further areas of applicability will become apparent from the description provided herein.It should be understood that the description and specific examples are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order that the present disclosure may be better understood, various forms of the present disclosure given by way of example will now be described with reference to the accompanying drawings, in which:
[0013] Figure 1 is a cross-sectional view of a bumper for impact absorption according to one form of the present disclosure.
[0014] 100: Bumper
[0015] 10: Resin composite materials
[0016] 20: Porous metal
[0017] The drawings described herein are for illustration purposes only and are not intended to limit the scope of the present disclosure in any way. DETAILED DESCRIPTION
[0018] The following description is merely exemplary in nature and is not intended to limit the present disclosure, application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate similar or corresponding parts and features.
[0019] Hereinafter, the present disclosure will be described in detail.
[0020] Method of manufacturing a bumper for impact absorption
[0021] The method for manufacturing a bumper for impact absorption according to the present disclosure includes: a first operation of filling a solid salt in a mold, injecting a molten metal into the mold, and solidifying the molten metal together with the solid salt to obtain a solidified product; a second operation of spraying water onto the solidified product to dissolve the solid salt to obtain a porous metal having pores; a third operation of arranging the porous metal in an injection mold; and a fourth operation of injecting-inserting a resin composite material into the injection mold to surround the porous metal while filling at least a portion of the pores in the porous metal.
[0022] First Operation
[0023] In the first operation, the mold is filled with solid salt, and molten metal is injected into the mold, and the molten metal is solidified together with the solid salt to obtain a solidified product. Here, the molten metal may be injected into the mold to fill the gaps between the solid salts to be solidified.
[0024] The solid salts are not particularly limited as long as they are water-soluble solid salts. For example, the solid salt may include a salt selected from KCl, NaCl, K 2 NO 3 、Na 2 CO 3 , CaCl 2 and MgCl 2 At least one of. Specifically, the solid salt may include salt.
[0025] In addition, each of the solid salts may have a particle shape and may have an average diameter (D 50 Specifically, the average diameter (D 50 ) is 2 to 8 mm, 3 to 7 mm, or 4 to 6 mm. When the average diameter of the solid salt is less than 1 mm, the porous metal to be manufactured has a porosity of 20% or less and a porosity of 1.3 g / cm 3or greater density, which is not suitable for reducing the weight of the vehicle. In addition, the diameter of each pore of the porous metal to be manufactured is so small that the injected resin composite material cannot flow into the porous metal, making it difficult to increase the impact absorption efficiency through the combination between the porous metal and the resin composite material. When the average diameter of the solid salt is 10mm or greater, the diameter of each pore of the porous metal to be manufactured becomes too large to reduce the impact absorption efficiency of the bumper to be manufactured, and a flow vortex is generated in the gap when the resin composite material is injected, thereby deteriorating the fluidity of the resin composite material.
[0026] Further, a sieve can be used to control the average diameter (D 50 ).
[0027] In addition, in the first operation, the solid salt can fill the mold, and the mold can be shaken to increase the packing ratio of the solid salt in the mold. Here, the mold filled with the solid salt can be shaken and the solid salt can move to increase or maximize the packing ratio of the solid salt.
[0028] In addition, the molten metal may include at least one metal selected from aluminum, silicon, magnesium, iron, nickel and manganese. Specifically, the molten metal may include aluminum.
[0029] In addition, the molten metal may be obtained by dissolving the above metals at 650°C to 750°C or 670°C to 720°C.
[0030] In addition, in the first operation, when the molten metal is injected into the mold, the molten metal can fill the gaps between the solid salts due to gravity. Here, the injection can be performed under compression or decompression to have a pressure of 0.5 to 0.9 bar or 1.2 to 2.0 bar. When the pressure is reduced or pressurized to the above pressure during injection, the following effect is achieved: the fine gaps between the solid salts or the fine gaps between the solid salt and the mold can be filled with the molten metal.
[0031] In addition, the curing may be performed at room temperature, specifically, at a temperature of 20° C. to 25° C. Here, the curing time is not particularly limited.
[0032] Furthermore, the solidified product may be in a form in which a solid salt is dispersed in a metal.
[0033] Second Operation
[0034] In the second operation, water is sprayed onto the solidified product to dissolve the solid salt, thereby obtaining a porous metal having pores. As described above, when a porous metal is manufactured using a solid salt and water, the average diameter of the pores in the porous metal can be easily adjusted to the average diameter of the solid salt. The chemical foaming process is a conventional method for manufacturing porous metals, which uses a foaming agent or thickener, such as TiH 2 MgH 2 Or CaO. The foaming agent or thickener as described above is retained on the surface of the porous metal to fall off or break from the surface of the metal. At the same time, since the porous metal manufactured by the method according to the present disclosure does not include a chemical foaming process, there is no problem of the compound retained on the surface of the porous metal breaking or falling off.
[0035] Here, in the second operation, water of 80 to 100° C. may be sprayed at 20 to 100 bar. Specifically, in the second operation, water of 80 to 95° C. may be sprayed at 30 to 80 bar or 40 to 60 bar.
[0036] In addition, in the second operation, water can be sprayed while shaking the solidified product. Here, water can dissolve the solid salt to form a porous metal with pores, each of which has an open cell type. In the porous metal, the solid salt can be dissolved, leaving only the metal. That is, the porous metal can be a metal with pores, each of which has an open cell type.
[0037] In addition, the porosity of the porous metal may be 20% to 60%. Specifically, the porosity of the porous metal may be 30% to 60% or 35% to 50%. When the porosity of the porous metal is 20% or less, the density of the porous metal is 1.3 g / cm 3 In addition, when the porosity of the porous metal is 60% or more, the energy absorption rate of the porous metal to be manufactured is reduced, and the collision absorption characteristics required for the bumper are not satisfactory, so it may be difficult to apply to the front bumper.
[0038] In addition, the density of the porous metal can be 1.1 to 1.3 g / cm 3 Specifically, the density of the porous metal can be 1.2 to 1.3 g / cm 3 When the density of the porous metal is within the above range, the density is similar to that of a conventional GMT, thereby contributing to reducing the weight of a vehicle.
[0039] Third Operation
[0040] In a third operation, the porous metal is arranged in an injection mold.
[0041] The porous metal may be cut into a size suitable for the size of the injection mold before being placed in the injection mold. Here, the cutting may be performed without any particular limitation as long as it is a method of cutting the porous metal.
[0042] Fourth Operation
[0043] In a fourth operation, the resin composite material is injected to be inserted into the injection mold to surround the porous metal while filling at least a portion of the pores in the porous metal.
[0044] Here, the resin composite material may include 50 to 90 parts by weight of a thermoplastic polymer and 10 to 50 parts by weight of a filler. Specifically, the resin composite material may include 50 to 80 parts by weight or 50 to 70 parts by weight of a thermoplastic polymer and 20 to 50 parts by weight or 30 to 50 parts by weight of a filler. When the amount of the thermoplastic polymer and the filler in the resin composite material is within the above range, the following problems can be prevented: the tensile strength of the bumper to be manufactured is insufficient, making it difficult to be applied to the front bumper, and the following problems can be prevented: the bonding force between the thermoplastic polymer and the filler is reduced, making it difficult to be manufactured into a bumper shape.
[0045] In addition, the thermoplastic polymer may be at least one selected from polyamide, polypropylene, polyethylene, polyethylene terephthalate, polyacetate, and acrylonitrile-butadiene-styrene. Specifically, the thermoplastic polymer may include polypropylene.
[0046] In addition, the filler may include at least one selected from glass fiber, carbon fiber and aramid fiber. Specifically, the filler may be glass fiber.
[0047] In addition, the filler may have a diameter of 1 to 100 μm and a length of 1 to 10 mm. Specifically, the filler may have a diameter of 5 to 80 μm or 10 to 30 μm and a length of 1 to 8 mm or 2 to 5 mm.
[0048] In the method for manufacturing a bumper for impact absorption according to the present disclosure as described above, inexpensive solid salt and water are used to manufacture porous metal to improve the economic benefits of the bumper to be manufactured due to low manufacturing cost. In addition, in the above-mentioned manufacturing method, the size of each pore of the porous metal can be adjusted by controlling the diameter of each solid salt, and since foaming by chemical reaction is not performed, the strength of the manufactured porous metal is excellent.
[0049] Bumper for impact absorption
[0050] A bumper for impact absorption according to the present disclosure may include a porous metal and a resin composite material, wherein the resin composite material surrounds the porous metal while filling at least a portion of pores in the porous metal.
[0051] Reference Figure 1 , a bumper 100 for impact absorption may include a porous metal 20 and a resin composite material 10 surrounding the porous metal 20 .
[0052] Here, the porous metal may have a porosity of 20% to 60% and a 3 Specifically, the porous metal may have a porosity of 30% to 60% or 35% to 50%, and a density of 1.2 to 1.3 g / cm 3 density.
[0053] Further, the resin composite material may include a thermoplastic polymer and a filler. Specifically, the resin composite material may include 50 to 90 parts by weight of a thermoplastic resin and 10 to 50 parts by weight of a filler.
[0054] In addition, the thermoplastic polymer may include at least one selected from the group consisting of polyamide, polypropylene, polyethylene, polyethylene terephthalate, polyacetate, and acrylonitrile-butadiene-styrene.
[0055] The filler may include at least one selected from glass fiber, carbon fiber, and aramid fiber.
[0056] In addition, the bumper for impact absorption may include 30 to 60 area % of porous metal and 40 to 70 area % of resin composite material based on the total area of the bumper cross section. Specifically, the bumper for impact absorption may include 50 to 60 area % of porous metal and 40 to 50 area % of resin composite material based on the total area of the bumper cross section. When the area of the porous metal is within the above range, the maximum load and energy absorption efficiency target values as the desired characteristics of the bumper can be met.
[0057] In addition, the bumper for impact absorption may have an energy absorption rate of 37% or more, 37% to 50%, or 40% to 50%.
[0058] Furthermore, the bumper for impact absorption may have a maximum load of 23 kN or more, 23 to 30 kN, or 25 to 30 kN.
[0059] The bumper for impact absorption according to the present disclosure as described above is lighter than a conventional steel bumper, which is advantageous in reducing the weight of a vehicle, and is excellent in impact energy absorption efficiency so as to be applied to a front bumper.
[0060] Hereinafter, the present disclosure will be described in more detail by way of examples. However, these examples are provided only for understanding the present disclosure, and the scope of the present disclosure is not limited to these examples in any sense.
[0061] [Example]
[0062] Example 1. Production of bumper
[0063] 1-1: Fabrication of porous metal
[0064] The average diameter (D 50 ) are placed in a mold, and molten aluminum at 700±20°C is injected into the mold so that the gaps between the salt particles and the gaps between the salt particles and the mold are filled with molten aluminum. Thereafter, a solidified product in which the salt particles are dispersed in the metal is obtained by solidification. Then, while shaking the solidified product, water at 90±5°C is sprayed at a high pressure of 50 bar to dissolve the salt particles, thereby obtaining a porous metal having pores, each of which is an open-pore type. The obtained porous metal has a carbon content of 1.25 g / cm 3 density, 40% porosity and an average thickness of about 150 mm.
[0065] 1-2: Bumper manufacturing
[0066] After the porous metal manufactured in Example 1-1 is placed in an injection mold, a resin composite material (40wt% of glass fiber (average diameter: 30μm, average length: 3.5mm) and 60wt% of polypropylene (weight average molecular weight: 55g / mol)) is injected to insert it into the injection mold for manufacturing a bumper for shock absorption. The obtained bumper has a shape in which the resin composite material fills a part of the pores in the porous metal.
[0067] Comparative Example 1.
[0068] 900g of aluminum as a raw material, 30g of sodium as a thickener, and 40g of ZrH as a foaming agent were added. 2 After mixing with 30g of cobalt, the mixture was placed in a mold. After that, the mold was solidified, melted and foamed at 700°C, and then cooled to room temperature. Thereafter, the mold was removed to obtain foamed aluminum.
[0069] Test Example 1. Measurement of physical properties of bumper
[0070] The maximum load and energy absorption rate of the bumpers manufactured in Example 1 and Comparative Example 1 were measured and the results are shown in Table 1.
[0071] Specifically, the maximum load and energy absorption rate are measured using a method similar to the vehicle condition test, which is a high-speed drop impact test performed by a load measuring sensor.
[0072] [Table 1]
[0073]
[0074] As shown in Table 1, it was found that the bumper of Example 1 was significantly superior to the bumper of Comparative Example 1 in terms of maximum load and energy absorption rate.
[0075] The bumper for impact absorption according to the present disclosure is lighter than a conventional steel bumper, which is advantageous in reducing the weight of a vehicle, and is excellent in impact energy absorption efficiency, and thus can be applied to a front bumper.
[0076] In addition, in the method for manufacturing a bumper for impact absorption according to the present disclosure, inexpensive solid salt and water are used to manufacture porous metal to improve economic efficiency. In addition, in the manufacturing method, the size of each gap in the porous metal can be easily adjusted by controlling the diameter of each solid salt, and the porous metal manufactured without foaming by chemical reaction is excellent in strength.
[0077] Although the present disclosure has been described above with reference to exemplary forms and drawings, the present disclosure is not limited thereto, but rather various modifications and changes may be made to the present disclosure by those skilled in the art without departing from the spirit and scope of the present disclosure.
Claims
1. A method for manufacturing a bumper for impact absorption, the method comprising: filling a solid salt in a mold, injecting a molten metal into the mold, and solidifying the molten metal with the solid salt together with the solid salt to obtain a solidified product; spraying water onto the solidified product to dissolve the solid salt, thereby obtaining a porous metal having pores; placing the porous metal in an injection mold; and A resin composite material is injection-inserted into the injection mold to surround the porous metal while filling at least a portion of the pores in the porous metal.
2. The method according to claim 1, wherein each of the solid salts comprises at least one selected from the group consisting of KCl, NaCl, K2NO3, Na2CO3, CaCl2 and MgCl2.
3. The method according to claim 1, wherein each of the solid salts has a granular shape and has an average diameter D of 1 mm to 10 mm. 50 .
4. The method according to claim 1, wherein the solidified product is in a form in which the solid salt is dispersed in the metal. 5 . The method according to claim 1 , wherein the injecting of the molten metal into the mold is performed under compression or decompression to have a pressure of 0.5 to 0.9 bar or 1.2 to 2.0 bar. The method according to claim 1 , wherein the porous metal has a porosity of 20% to 60%. 7 . The method according to claim 1 , wherein when the water is sprayed, water at 80° C. to 100° C. is sprayed at 20 to 100 bar. 8 . The method of claim 1 , wherein the resin composite material comprises 50 to 90 parts by weight of a thermoplastic polymer and 10 to 50 parts by weight of a filler.
9. The method according to claim 8, wherein the thermoplastic polymer comprises at least one selected from the group consisting of polyamide, polypropylene, polyethylene, polyethylene terephthalate, polyacetate, and acrylonitrile-butadiene-styrene, and The filler comprises at least one selected from glass fiber, carbon fiber and aramid fiber.
Citation Information
Patent Citations
Bumper back-beam for vehicles
KR101683511B1
Water supplying control unit and cooling apparatus having thereof
KR1020190069190A
Porous metal treating fluid and preparation method of composite material
CN104152904A
Polymer / foamed aluminum composite material for automobile bumper and preparation process for polymer / foamed aluminum composite material
CN105462029A
Networked damping vibration attenuation composite and preparation method thereof
CN105479855A